Effects of whole-body vibration training on muscle performance in healthy women: A systematic review and meta-analysis of randomized controlled trials - Bopeng Qiu; Ziyu Wang; Mingyue Yin; Jinghan Feng; Penglin Diao; Juan Del Coso; Redha Taiar (PLoS ONE, 2025)
Objective This study aimed to perform a comprehensive meta-analysis of randomized controlled trials examining the effectiveness of whole-body vibration training (WBVT) on muscle performance in healthy women. Methods A systematic search of studies available up to 30 May 2024 was conducted using seven databases, including PubMed, EMBASE, Web of Science, Scopus, CINAHL, PEDro, and the Cochrane Library. Studies with a randomized and controlled protocol in which the effect of WBVT on muscle performance variables was compared to that of a) a non-exercise intervention or b) exercise intervention in healthy women were assessed for eligibility. The methodological quality of the included studies was assessed using the PEDro scale. Meta-analyses were performed using random effects models, and the results were expressed as standardized mean differences (SMDs) with corresponding 95% confidence intervals (95% CIs). Results A total of 21 randomized controlled trials, encompassing 748 healthy women, was included in the meta-analysis. WBVT demonstrated significantly greater effects on muscle strength and power when compared with the non-exercise control groups with regard to knee extension (SMD = 0.534, 95% CI: 0.303 to 0.766, p < 0.001), leg press (SMD = 0.794, 95% CI = 0.424 to 1.163, p < 0.001), ankle plantar flexion (SMD = 0.462, 95% CI: 0.019 to 0.904, p = 0.041), and the countermovement jump performance (SMD = 0.470, 95% CI: 0.211 to 0.729, p < 0.001). However, WBVT significantly improved only the countermovement jump performance (SMD = 0.338, 95% CI: 0.037 to 0.640, p = 0.028) when compared with the exercise control groups. Subgroup analyses revealed that longer periods (≥ 12 weeks) of WBVT resulted in greater benefits for both muscle strength and power compared to the non-exercise control group. Additionally, higher frequencies (> 30 Hz, SMD = 0.736, p < 0.001; ≤ 30 Hz, SMD = 0.284, p = 0.109) provided greater benefits for improving muscle strength. Last, post-menopausal women (post-menopausal, SMD = 0.561, p = 0.001; pre-menopausal, SMD = 0.354, p = 0.076) obtained greater benefits in muscle power with WBVT than pre-menopausal women. Conclusions WBVT is efficacious in improving lower-body muscle strength and power in healthy women. However, the potential benefits of WBVT compared to other exercise interventions were only associated with an enhancement in countermovement jump performance. Longer periods (≥ 12 weeks) of WBVT resulted in greater benefits for both muscle strength and power compared to the non-exercise control group. Additionally, higher vibration frequencies (> 30 Hz) provided greater improvements in muscle strength, while post-menopausal women reaped greater benefits in muscle power than pre-menopausal women.